Histological patterns, subtypes and aspects of prostate cancer: different aspects, different outcomes. Issue 6 (8th September 2022) - Wasinger, Gabriel; Oszwald, André; Shariat, Shahrokh F.; Compérat, Eva
Abstract : Purpose of review: The most common prostatic cancers (PCa) are acinary adenocarcinomas. Histological subtypes have been variably defined. The purpose of this review is to discuss unusual histological patterns and subtypes of acinar adenocarcinoma, as well as other types of PCa and their prognostic and therapeutic relevance. Recent findings: The new term 'subtype' for morphologically defined tumor entities replaced the term 'variant' in the new 2022 classification of the WHO to allow for clear terminological distinction from genetic variants. The 2022 WHO classification mentions prostatic intraepithelial neoplasia (PIN)-like carcinoma, signet-cell-like adenocarcinoma, sarcomatoid carcinoma and pleomorphic-giant-cell adenocarcinoma of the prostate as true subtypes of acinary PCa. Other forms of acinary PCa are termed unusual histological patterns and include atrophic, foamy-cell, microcystic, pseudohyperplastic and mucinous patterns. Nonacinar forms of prostate cancer include other glandular PCa, the ductal adenocarcinoma and the treatment-associated neuroendocrine carcinoma, and nonglandular PCa, the adenosquamous carcinoma, the squamous cell carcinoma and the adenoid cystic (basal cell) carcinoma of the prostate. Summary: True subtypes of acinary PCa and other forms of glandular and nonglandular PCa show relevant differences in prognosis and treatment approach compared with classic acinary PCa. The relevance of unusual histological patterns mainly lies in their deceptive benign appearance and the need for pathologists to know about these entities for accurate and timely diagnosis.